A Study Of Customers' Expectations In Online Shopping - Tee, Puat Beng (2008)
This study addresses the expectations that e-commerce consumers would like to achieve when they shop online, and how e-commerce retailers can influence consumers to buy online. The constructs of the study include purchase convenience, product quality, product pricing and information security, which were used to test the influences that these factors have with regards to consumers' online shopping expectations.